Comparative sustainability assessment of hybrid desalination systems for freshwater production - Nadira Salsabila; Asifa Anwar; Haya Talib Shubbar; M. Imran Khan; Tareq Al-Ansari; Yusuf Bicer (Energy Nexus)
Water scarcity is one of the most critical global challenges, with nearly 4 billion people affected by acute water shortages. Desalination has emerged as a key solution to meet the growing demand for freshwater, especially in arid regions. However, standalone conventional desalination technologies such as multi-stage flash (MSF) and reverse osmosis (RO) face challenges in terms of high energy consumption, low water recovery rates in some cases, and certain environmental impacts, which hybrid desalination systems can mitigate. Despite the growing interest in hybrid desalination technologies, there is a gap in their sustainability analysis, making it difficult to determine the most sustainable option for freshwater production. Therefore, this study conducts a comprehensive sustainability assessment of seven different hybrid desalination configurations with double-stage RO as the control. The analysis focuses on key indicators of sustainability, including energy efficiency, water recovery, environmental impacts, and social acceptance of the produced freshwater. The results reveal that the RO system, when combined with multi-effect distillation (MED), had a global sustainability index (GSI) of 83 %, which is the most sustainable configuration, outperforming RO-RO (GSI of 75 %). In contrast, the MSF-RO system ranks the lowest with a GSI of 24 %, due to its high energy consumption and carbon emissions. The study highlights the potential of hybrid systems, particularly RO-MED, to address water scarcity more sustainably. These findings offer practical guidance for policymakers and industry stakeholders in selecting desalination technologies that balance water security, energy efficiency, and environmental impact. Future research should explore integrating renewable energy sources into hybrid systems to further reduce environmental impacts.